Muscle stiffness in tension-type headache patients with pericranial tenderness: A shear wave elastography study. (9th April 2018) - Kolding, Lærke Tørring; Do, Thien Phu; Ewertsen, Caroline; Schytz, Henrik Winther
Background: Tension-type headache patients have previously been shown to have increased muscle tone, stiffness and tenderness in the trapezius muscle compared to healthy volunteers. Shear wave elastography is a non-invasive method to measure muscle stiffness. The aim of the study was to use shear wave elastography to investigate if tension-type headache patients had increased pericranial muscle stiffness and whether pericranial muscle stiffness correlated to muscle tenderness. Methods: Seventeen patients with very frequent or chronic tension-type headache associated with pericranial tenderness and 29 healthy volunteers were included. Muscle stiffness was measured using shear wave elastography and muscle tenderness was measured using local tenderness score and total tenderness score. Results: There was no statistically significant difference in muscle stiffness between tension-type headache patients and healthy volunteers. The local tenderness and total tenderness scores were higher in tension-type headache patients compared with healthy volunteers. There was no correlation between muscle stiffness and tenderness. Conclusion: We found no sign of increased pericranial muscle stiffness in tension-type headache patients compared with healthy volunteers using shear wave elastography. Our findings do not suggest a generalized pericranial increase in muscle tone in very frequent and chronic tension-type headache patients.